Saya Pasti Bisa: Speech Act Analysis in Merry Riana Motivation Video Through Searle Theory - Fadhilah, Jihan; Muslim, M Umar (Universitas Muria Kudus, 2023)
Sebuah ujaran pasti memiliki konteks. Mengingat bahwa ujaran pasti memiliki kepentingan, kita harus memahami konteks apa yang mendasari terbentuknya sebuah ujaran, untuk apa ujaran tersebut dikonsumsi, dan aspek apa saja yang ada di dalam ujaran hingga mempengaruhi pembentukannya. Pada artikel ini, peneliti akan melengkapi penelitian-penelitian sebelumnya dengan data ujaran motivasi. Teori yang digunakan adalah teori tindak tutur Searle dan metode yang digunakan adalah deskriptif kualitatif dengan pendekatan teknik analisis konten karena data yang akan diteliti memerlukan penjelasan secara deskriptif. Penelitian ini menemukan sembilan tindak tutur representatif, satu tindak tutur ekspresif, satu tindak tutur komisif, tujuh tindak tutur deklaratif dan tujuh tindak tutur direktif. Tindak tutur yang paling banyak muncul dari ujaran motivasi adalah tindak tutur representatif.An utterance must have context. Given that utterances certainly have importance, researchers must understand what context that underlies the formation of an utterance, what the utterance is consumed for, and what are the aspect of utterance that influence its formation. Pragmatic analysis, especially about speech acts, brings us deeper into not only the content in a text but also the meaning, what message is conveyed, the reasons why the message is conveyed, and how the meaning of the message is understood by humans. In this article, the researcher will complement previous studies with data on motivational utterances. The theory used is Searle's speech act theoryan American philosopher who inherits, revises, and develops speech act theory. Not only that, Searle also disseminated and received widespread attention about this theory in philosophical circles, linguistic activists and made it the core theory in the fields of western philosophy and linguistics, especially in pragmatics. and the method used is descriptive qualitative with a content analysis technique approach because the data to be examined requires descriptive explanation. This study found nine representative speech acts, one expressive speech act, one commissive speech act, seven declarative speech acts and seven directive speech acts. The speech act that appears the most in motivational utterance is the representative speech act.